2001
DOI: 10.1007/pl00001826
|View full text |Cite
|
Sign up to set email alerts
|

Lignoid chemical defenses in the freshwater macrophyte Saururus cernuus

Abstract: Chemical defense against herbivores has rarely been investigated for freshwater plants, possibly due to the common misconception that herbivory on aquatic macrophytes is low and would not select for chemical defenses. In previous work, the freshwater angiosperm Saururus cernuus was shown to be a low preference food for omnivorous crayfish despite its high nutrient value and relatively soft texture. We used feeding by the crayfish Procambarus clarkii to guide fractionation of the deterrent lipid-soluble extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 57 publications
2
20
0
Order By: Relevance
“…Not many studies have yet investigated chemical defenses in submerged freshwater angiosperms. Many studies have focused on marine macroalgae (Hay 1996;Paul et al 2006) and emergent or floating-leaved freshwater angiosperms Dorn et al 2001;Kubanek et al 2001;Prusak et al 2005). These studies often used omnivorous crustaceans as grazers, against which extracts of submersed species have turned out to be inactive Prusak et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not many studies have yet investigated chemical defenses in submerged freshwater angiosperms. Many studies have focused on marine macroalgae (Hay 1996;Paul et al 2006) and emergent or floating-leaved freshwater angiosperms Dorn et al 2001;Kubanek et al 2001;Prusak et al 2005). These studies often used omnivorous crustaceans as grazers, against which extracts of submersed species have turned out to be inactive Prusak et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…So far, only a few studies have addressed feeding deterrents in submersed freshwater plants, and studies with herbivorous freshwater insects are especially rare (see Dorn et al 2001). Mostly crayfish have been used in bioassays, as these omnivores feed in a wide variety of laboratory assays (Lodge 1991;Kubanek et al 2001). Thus far, nobody has succeeded in rearing Acentria or other aquatic lepidoptera on food other than submersed macrophytes.…”
Section: Introductionmentioning
confidence: 99%
“…4,5) The antifeedant activity of (À)-DGA in crayfish has also been reported. 6) However, whether DGA and SECO demonstrate insecticidal activity and whether this activity varies in relation to their structure has remained unknown. The insecticidal activity of lignans against larvae of the Culex pipiens mosquito was therefore measured to extend our knowledge of the structureactivity relationships of lignans.…”
mentioning
confidence: 99%
“…To date, 22 species of freshwater macrophytes have been demonstrated to produce chemical defenses against herbivores (Newman et al 1996;Cronin 1998;Kubanek et al 2001;Cronin et al 2002;Prusak et al 2005;Parker et al 2006Parker et al , 2007Miller and Provenza 2007;Erhard et al 2007), and 3 species have been shown to induce either structural defenses (Center and Van 1989;Kouki 1993) or an unidentiWed defense (JeVries 1990), but only 1 species (Nuphar luteum) is known to induce a chemical defense . The chemicals responsible for this induced defense were not identiWed and the physiological eVects on herbivores were not investigated .…”
Section: Introductionmentioning
confidence: 99%